O uso das mídias digitais como ferramenta de ensino da Língua portuguesa - ALMEIDA, Aline Rocha de (2019)
The objective of this paper is to verify which form the digital media are used for the teaching of the Portuguese language, having as a research scenario a class of 9th grade of the School of Basic Education São Francisco Xavier in the municipality of Barcarena-PA. Among the specific objectives were to verify the teaching methodologies that include digital media in Portuguese language classes, to identify the digital genres that are worked in the classroom and to evaluate the students' level of mastery over digital technologies. The study was carried out based on a bibliographical research that will be presented in the theoretical basis, focusing on the ideas of several researchers in the area, such as KENSKI (2012) and SOARES (2002), and conducting qualitative research that used as instruments of data collection. Questionnaire developed and applied to the students and interview with the Portuguese teacher of the class and as documentary source the Portuguese language teaching plan. In the qualitative research of the Portuguese language teaching process, there are three aspects that should be considered, the first is the teaching plan of the Portuguese language course and how its applicability in the classroom is made; the second strand is the students who are in the process of transition from elementary to middle school and make up a current generation driven by technology and by all the emerging factors in social networks and the third is the teachers, analyzing how digital media participate in the school environment and what methodologies are used as a teaching tool. It was observed that the curriculum includes in its curriculum the inclusion of digital genres, such as: multimodal texts, slogans and infographics. Students have access to digital media through their personal cellular device, however, they are used in a merely instrumental way, however, aspire to schools that train their teachers in digital technologies, making them willing to overcome the barriers that the public school faces, leading them to disconnect from obsolete pedagogical practices, connecting these students to the new age, new genres and new technologies.